Experimental and numerical investigation of the cylinder-dome transition region of a pressure vessel - E. Özaslan (Composites Part C: Open Access, 2021)
The difference in stiffness between cylindrical and dome regions of a filament wound composite pressure vessel may cause undesirable bending in the cylinder-dome transition region. Because of the bending, strain distribution may be non-uniform in the transition region. Therefore, accurate modeling that captures non-uniform strain distribution in the transition region is crucial for a safe pressure vessel design. In this study, a pressure vessel with a metallic liner was designed. Three identical pressure vessels were manufactured. One of the vessels was cut for detailed geometric investigation. The section of the transition region was investigated using an optical microscope. The termination of each hoop layer and resin pockets under the helical layers were clearly observed at the micro-scale. Also, measurement of layer by layer thickness and fiber volume fraction were performed. Other vessels were pressurized until the burst pressure. Fiber direction strain was measured using strain gauges that were mostly attached to the transition region to capture the non-uniform strain distribution. Two finite element models were created to analyze the transition region. The first finite element model was created with design parameters. The second finite element model was established by considering the findings obtained from the microscopic analysis. Strain distributions obtained from the strain gauges and finite element analyses were compared. In contrast to the first finite element model, strain distribution in the transition region was perfectly matched with the second finite element model. Thus, important aspects of analyzing the transition region of a pressure vessel were addressed for designers.